Superplasticized concrete and method for making same

CN118724530BActive Publication Date: 2026-10-30西安市政道桥建设集团有限公司 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410802321.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2026-10-30
Estimated Expiration
2044-06-20

AI Technical Summary

Technical Problem

[0004]针对上述中的相关技术,发明人发现虽然缓凝剂能延长混凝土的凝结时间,但添加过量,会使混凝土中的水分在较长时间内仍保持较高的粘度,导致混凝土的流动性降低,影响混凝土内原料的分布均匀性,在浇筑过程中,无法完全填充空隙,导致浇筑结构中存在空洞或空隙,降低混凝土的整体密实性

Benefits of technology

1、由于本申请采用十二烷基硫酸钠、葡萄糖酸钠、麦秸碱溶液等成分制备缓凝剂,不仅改善了混凝土的凝结时长,为后续施工提供足够的时间,而且增加了混凝土的流动性,增加混凝土的密实度,改善其抗压强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the field of building materials, and particularly discloses super-retarding concrete and a preparation method thereof. The super-retarding concrete comprises the following raw materials in parts by weight: 165-175 parts of water, 160-260 parts of cement, 983-1000 parts of stone, 830-845 parts of sand, 110-160 parts of admixture, 3-6 parts of retarding agent, 2-5 parts of preservative, and 10-20 parts of lubricant. The retarding agent comprises the following raw materials in parts by weight: 150-200 parts of wheat straw alkali solution, 150-200 parts of slump retaining agent, 60-80 parts of white sugar, 30-50 parts of sodium gluconate, 0.05-0.08 parts of sodium dodecyl sulfate, and 0.05-0.1 parts of hydroxypropyl methylcellulose. The super-retarding concrete has the advantages of prolonged setting time, good fluidity of the concrete, high compactness, and small dry shrinkage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of building materials technology, and more specifically, to an ultra-retarded concrete and its preparation method. Background Technology

[0002] With the advancement of urbanization in my country, ultra-high, ultra-deep, and ultra-large-scale construction projects are constantly emerging, thus placing higher demands on concrete technology. In the construction of bored interlocking piles for deep foundation pit support structures such as subways and railway stations, the initial setting time of the concrete is required to reach more than 60 hours, and it must have sufficient later-stage strength. This necessitates the technical requirements for ultra-retarded concrete. Ultra-retarded concrete is a new type of concrete specially formulated to meet specific construction requirements, with an initial setting time of 60-80 hours and a 28-day strength not lower than the design strength grade. The development and application of ultra-retarded concrete can satisfy the diversification of concrete construction technologies.

[0003] In the prior art, Chinese invention patent application document with application number CN202310152010.6 discloses an ultra-retarded concrete, which includes the following raw materials in parts by weight, including the following components in parts by weight: 390-450 parts of cementitious material; 720-840 parts of sand; 920-1080 parts of crushed stone; 9-13 parts of water-reducing agent; 8-12 parts of retarder; and 150-200 parts of water; wherein, the cementitious material includes cement, fly ash and slag powder in a weight ratio of (280-320):(70-90):(37-57).

[0004] Regarding the aforementioned technologies, the inventors discovered that although retarders can extend the setting time of concrete, excessive addition will cause the water in the concrete to maintain a high viscosity for a longer period of time, resulting in reduced concrete fluidity and affecting the uniformity of the distribution of raw materials within the concrete. During the pouring process, the voids cannot be completely filled, leading to voids or gaps in the poured structure and reducing the overall density of the concrete. Summary of the Invention

[0005] To improve the fluidity and density of retarded concrete, this application provides an ultra-retarded concrete and its preparation method.

[0006] In the first aspect, this application provides an ultra-retarded concrete, which adopts the following technical solution: An ultra-retarded concrete comprises the following raw materials in parts by weight: 165-175 parts water, 160-260 parts cement, 983-1000 parts aggregate, 830-845 parts sand, 110-160 parts admixture, 3-6 parts retarder, 2-5 parts corrosion inhibitor, and 10-20 parts lubricant. The retarder comprises the following raw materials in parts by weight: 150-200 parts wheat straw alkali solution, 150-200 parts slump retainer, 60-80 parts white sugar, 30-50 parts sodium gluconate, 0.05-0.08 parts sodium dodecyl sulfate, and 0.05-0.1 parts hydroxypropyl methylcellulose.

[0007] By adopting the above technical solutions, cement and water form cement paste, which coats the surface of gravel and sand and fills their voids. The cement paste easily hardens in air and can bind sand, gravel, and other materials together. Retarders are prepared using sodium gluconate and sodium dodecyl sulfate. Sodium gluconate has good compatibility with cement, effectively controlling concrete settling time. It also works well with sugar, is inexpensive, and is non-toxic and harmless. Sodium dodecyl sulfate is used as an air-entraining agent. As a hydrophobic surfactant, its activity mainly occurs at the water-air interface. The hydrophilic groups insert into the water, and the hydrophobic groups insert into the air, reducing surface tension and forming bubbles. This introduces a large number of tiny, uniform bubbles, which act as a lubricant, improving the fluidity of concrete and reducing segregation and bleeding. Furthermore, the bubbles introduced by sodium dodecyl sulfate have a diameter in the micrometer range. It effectively seals harmful channels and reduces seepage channels. When concrete freezes, it can absorb expansion stress, improve the impermeability and frost resistance of concrete, and thus improve the durability of concrete. Hydroxypropyl methylcellulose, as a water-retaining agent, thickener and binder, can improve the cohesiveness between concrete slurries and reduce segregation and bleeding. In an alkaline environment, the ether bonds of the continuous lignin structural units of wheat straw break, and the saponification reaction breaks the ester bonds linking hemicellulose and cellulose as well as the hydrogen bonds between hemicellulose and cellulose. Hemicellulose and lignin in wheat straw continuously dissolve and decompose into monosaccharides. The hydrolyzed monosaccharides dissolve in water and are converted into sugar acids, which contain many hydroxyl functional groups. In an alkaline medium, they react with calcium ions formed by cement hydration to form calcium glycosides. Therefore, in the early stage of hydration, the concentration of calcium ions in the liquid phase is in an unsaturated state, which affects the hydration process of other components in silicate cement. Meanwhile, hydroxyl groups readily associate with water molecules via hydrogen bonds, adsorbing onto the surface of cement particles and hindering hydration in concrete. This results in a water film forming on the surface of the concrete particles. The system composed of wheat straw alkaline solution, cement, and slump retainer exhibits good compatibility, providing excellent slump retention and auxiliary plasticizing effects. This enhances the fluidity of concrete and hinders cement setting and hardening. Furthermore, the pentosan molecules and lignin in wheat straw readily adsorb onto the surface of hydrated cement particles, giving the hydrated cement particles and cement particles the same surface charge. Like charges repel each other, causing them to tend towards a dispersed state, improving the lubricity of cement particles, affecting cement setting and solidification, and providing a good retarding effect. In addition, the alkali-soluble substances in the wheat straw alkaline solution adsorb onto the aluminate phase, accelerating the hydrolysis of tricalcium aluminate and promoting the rapid formation of a large amount of ettringite, thus significantly enhancing the compressive strength of concrete. Furthermore, a certain amount of lubricant is added to increase slump and further improve the fluidity of concrete.

[0008] Optionally, the lubricant is prepared as follows: PTFE micro powder and polyalphaolefin are mixed evenly to prepare a matrix solution; Hexadecyltrimethylammonium bromide was added to a mixed solution of anhydrous ethanol and deionized water, and stirred to dissolve, thus obtaining a mixed solution. The matrix solution is added to the mixture, homogenized, sonicated, and the pH is adjusted to 10-11. The mixture is heated in a water bath to 80-85℃, tetraethyl orthosilicate is added, and the mixture is stirred for 1-2 hours. After cooling to room temperature, the mixture is filtered, washed, and dried to obtain the lubricant.

[0009] By adopting the above technical solution, PTFE micropowder possesses a perfluorocarbon surface, resulting in a low coefficient of friction. Furthermore, due to the small diameter and high electronegativity of fluorine atoms in polytetrafluoroethylene (PTFE), its ability to capture electrons is strong, and its symmetrical carbon-fluorine bond distribution can cancel out polarity. Therefore, PTFE has very low surface energy, giving it non-stick and hydrophobic properties. The molecular chains can undergo orientational movement, causing surface deformation and thus creating a lubricating effect. Polyalphaolefin (PAO) is a highly lubricating liquid base oil. When mixed with PTFE micropowder as a matrix solution, under alkaline conditions, the silicon source in tetraethyl orthosilicate gradually hydrolyzes to form silica. The silica surface contains a large number of hydroxyl groups, carrying negative... The charge, along with the amino group of hexadecyltrimethylammonium bromide, causes silica to coat the polyalphaolefin and PTFE micropowder through charge adsorption. After drying, this forms a silica outer wall. When the lubricant is mixed with concrete materials, the lubricant surface breaks due to mechanical collision and surface friction, releasing the polyalphaolefin and PTFE micropowder. Under the lubricating effect of the polyalphaolefin and PTFE micropowder, a self-lubricating film is formed between the concrete materials, effectively reducing the adhesion and aggregation between the materials and improving the lubrication effect. If polyalphaolefin and PTFE micropowder are added directly, the hydrophobic effect of the two may lead to uneven mixing of the concrete materials and segregation.

[0010] Optionally, the mass ratio of the PTFE micro powder to the polyalphaolefin is 0.2-0.4:1; The mass ratio of the matrix solution, hexadecyltrimethylammonium bromide, and tetraethyl orthosilicate is 1:0.3-0.35:1-1.2.

[0011] By adopting the above technical solution, PTFE micro powder and polyalphaolefin are mixed in the above mass ratio to prepare a matrix solution. When the silica outer wall formed after the hydrolysis of tetraethyl orthosilicate is broken under mechanical stirring, the polyalphaolefin can drive the PTFE micro powder to flow in the concrete, improving the lubrication of the concrete. The mixing of tetraethyl orthosilicate, matrix solution and hexadecyltrimethylammonium bromide in the above mass ratio can improve the coating effect of silica. When the silica outer wall is broken, silica, as a solid lubricant, can also play a role in reducing friction and lubrication.

[0012] Optionally, the admixture includes fly ash and PMMA microspheres in a mass ratio of 1:0.5-1.

[0013] By adopting the above technical solution, fly ash particles are round and have a smooth surface. They are chemically stable, not prone to surface deformation, and have virtually no hydration activity. They can act as fillers and also have a ball-bearing effect, reducing friction between particles and improving fluidity. PMMA microspheres are high molecular polymers formed by free radical polymerization of methyl methacrylate. Their molecular chains are soft and self-lubricating. Under pressure, they can offset the load through surface deformation. This not only improves the fluidity of concrete but also enhances its crack resistance and reduces drying shrinkage.

[0014] Optionally, the PMMA microspheres are prepared as follows: Hyaluronic acid is added to deionized water to obtain a hyaluronic acid solution; Chitosan, potassium persulfate, and methyl methacrylate are mixed and stirred evenly at 70-80℃ to obtain a polymer emulsion. The mass ratio of methyl methacrylate, chitosan, and potassium persulfate is 1:0.1-0.15:0.1-0.2. The polymer emulsion and hyaluronic acid solution were mixed at a mass ratio of 9-10:1, sodium dodecyl sulfate was added, and the mixture was stirred evenly. Then, under nitrogen protection, the mixture was reacted at 75-80℃ for 1.5-2 hours, and the temperature was raised to 85-90℃ for 1.5-2 hours. The mixture was then filtered and dried to obtain intermediate microspheres. The intermediate microspheres were added to a sodium hydroxide solution, heated to 80-85℃, stirred for 38-40 hours, filtered, washed until neutral, and dried to obtain PMMA microspheres.

[0015] Due to the addition of retarders, the hydration reaction time of cement in super-retarded concrete is prolonged, resulting in a reduction in the amount of hydration products generated within the same time frame. This leads to a relatively loose concrete structure and increases the likelihood of drying shrinkage. By employing the aforementioned technical solution, chitosan, which has good hygroscopic and moisturizing effects, is combined with PMMA to form a polymer emulsion. Hyaluronic acid, which also possesses excellent moisturizing properties, is dissolved in deionized water to obtain a hyaluronic acid solution. This solution is then blended with the polymer emulsion to obtain a blended emulsion, which forms microspheres with PMMA and chitosan as the shell and hyaluronic acid solution as the core. Under the action of an initiator, PMMA and chitosan form a network structure, thereby improving the coating rate of the hyaluronic acid solution. Furthermore, the high amount of chitosan added in this application causes cross-linking between the membrane molecules, which inhibits the release of the hyaluronic acid solution and slows down its release, thus prolonging its release rate and continuously providing moisture for the drying of the concrete, reducing the drying shrinkage of the concrete.

[0016] Optionally, the fly ash has a particle size of 32-35 μm, and the PMMA microspheres have a particle size of 65-70 μm.

[0017] By adopting the above technical solutions, fly ash and PMMA microspheres of the above particle size play a filling effect and a ball effect in concrete, which can increase the fluidity and density of concrete.

[0018] Optionally, the wheat straw alkali solution is obtained by crushing wheat straw, soaking it in sodium hydroxide solution, and then taking it out.

[0019] By adopting the above technical solution, the ether bonds connecting the lignin units in wheat straw are broken in an alkaline solution, thereby causing hemicellulose and lignin in wheat straw to continuously dissolve and form monosaccharides. After the monosaccharides dissolve in water, they are converted into sugar acids, which then form calcium sugar acid with the calcium ions formed by cement hydration, thus affecting the hydration process.

[0020] Optionally, the preservative is selected from at least one of nitrates, nitrites, sodium benzoate, and citric acid.

[0021] Optionally, the slump retainer is at least one of polycarboxylate slump retainers, aminosulfonate slump retainers, and naphthalene-based slump retainers.

[0022] Secondly, this application provides a method for preparing super-retarded concrete, which adopts the following technical solution: A method for preparing super-retarded concrete includes the following steps: Cement, gravel, sand, and admixtures are mixed evenly to obtain a dry mix. A composite additive is prepared by mixing retarder, preservative and lubricant; The composite admixture is added to the dry mix, mixed well, and then water is added and stirred evenly to obtain super-retarded concrete.

[0023] By adopting the above technical solution, cement and other raw materials are first mixed to form a dry mix, then retarders, corrosion inhibitors and lubricants are mixed, the obtained composite admixture is mixed with the dry mix, and finally water is added, which can improve the mixing uniformity of each raw material and improve the fluidity of concrete.

[0024] In summary, this application has the following beneficial effects: 1. Because this application uses sodium dodecyl sulfate, sodium gluconate, wheat straw alkali solution and other components to prepare the retarder, it not only improves the setting time of concrete, providing sufficient time for subsequent construction, but also increases the fluidity of concrete, increases the density of concrete, and improves its compressive strength.

[0025] 2. In this application, silica-coated polyalphaolefin and PTFE micro powder are preferably used as lubricants. Under mechanical stirring, the outer wall of silica breaks, releasing the internal polyalphaolefin and PTFE micro powder, thereby forming a lubricating film between the raw materials, improving the fluidity of concrete and increasing the compressive strength of concrete.

[0026] 3. In this application, chitosan and PMMA are cross-linked to form an outer network structure, which is then coated with hyaluronic acid solution to prepare PMMA microspheres. The PMMA microspheres play a filling and ball-beading effect in the concrete, increasing the fluidity and density of the concrete. Moreover, as the hyaluronic acid is continuously released, it continuously replenishes the moisture for the drying of the concrete, thereby reducing the drying shrinkage of the concrete. Detailed Implementation

[0027] The following embodiments provide a further detailed description of this application.

[0028] Examples of lubricant preparation 1-5

[0029] In the following preparation example 1, the PTFE micro powder was selected from Jinyunlai, Zhangmutou, Dongguan City, with model number L206 and particle size of 8μm, and the polyalphaolefin was selected from ExxonMobil, with model number PAO10.

[0030] Preparation Example 1: 0.48 kg of PTFE micro powder and 1.2 kg of polyα-olefin were mixed evenly to prepare a matrix solution; 0.588 kg of cetyltrimethylammonium bromide was added to a mixed solution of 1 kg of anhydrous ethanol and 9 kg of deionized water, and stirred to dissolve, thus obtaining a mixed solution. The matrix solution was added to the mixture, homogenized, sonicated, and the pH was adjusted to 11. The mixture was heated to 80°C in a water bath, 1.68 kg of tetraethyl orthosilicate was added, and the mixture was stirred for 2 hours. After cooling to room temperature, the mixture was filtered, washed with anhydrous ethanol and distilled water, and dried at 60°C for 24 hours to obtain the lubricant.

[0031] Preparation Example 2: 0.24 kg of PTFE micro powder and 1.2 kg of polyα-olefin were mixed evenly to prepare a matrix solution; 0.432 kg of cetyltrimethylammonium bromide was added to a mixed solution of 1 kg of anhydrous ethanol and 9 kg of deionized water, and stirred to dissolve, thus obtaining a mixed solution. The matrix solution was added to the mixture, homogenized, sonicated, and the pH was adjusted to 10. The mixture was heated to 85°C in a water bath, and 1.728 kg of tetraethyl orthosilicate was added. The mixture was stirred for 1 hour, cooled to room temperature, filtered, washed with anhydrous ethanol and distilled water, and dried at 60°C for 24 hours to obtain the lubricant.

[0032] Preparation Example 3: The difference from Preparation Example 1 is that an equal amount of polyalphaolefin was used instead of PTFE seed powder.

[0033] Preparation Example 4: The difference from Preparation Example 1 is that an equal amount of PTFE micro powder was used instead of polyalphaolefin.

[0034] Preparation Example 5: 0.48 kg of PTFE micro powder and 1.2 kg of polyalphaolefin were mixed evenly to prepare a lubricant.

[0035] Preparation of PMMA microspheres: Examples 6-10 Preparation Example 6: (1) 1.5 kg of hyaluronic acid was added to deionized water to obtain a hyaluronic acid solution with a concentration of 20 wt% and a molecular weight of 1000 kDa; (2) Mix 0.15 kg chitosan, 0.1 kg potassium persulfate and 1 kg methyl methacrylate, and stir evenly at 70 °C for 12 h to obtain a polymer emulsion. The mass ratio of methyl methacrylate, chitosan and potassium persulfate is 1:0.15:0.1, and the degree of deacetylation of chitosan is 95%. (3) The polymer emulsion and hyaluronic acid solution were mixed at a mass ratio of 10:1, sodium dodecyl sulfate was added, and the mixture was stirred for 2 hours. Then, under nitrogen protection, the mixture was reacted at 75°C for 2 hours, heated to 85°C, and reacted for 2 hours. The mixture was then filtered and dried under vacuum at 80°C to obtain intermediate microspheres. The amount of sodium dodecyl sulfate used was 10% of the total weight of the polymer emulsion and hyaluronic acid solution. (4) Add the intermediate microspheres to a 0.5 mol / L sodium hydroxide solution, heat to 85°C, stir for 40 h, filter, wash with distilled water until neutral, and dry at 70°C to obtain PMMA microspheres.

[0036] Preparation Example 7: (1) 1.5 kg of hyaluronic acid was added to deionized water to obtain a hyaluronic acid solution with a concentration of 20 wt% and a molecular weight of 1000 kDa; (2) Mix 0.1 kg chitosan, 0.2 kg potassium persulfate and 1 kg methyl methacrylate, and stir evenly at 70 °C for 12 h to obtain a polymer emulsion. The mass ratio of methyl methacrylate, chitosan and potassium persulfate is 1:0.1:0.2, and the degree of deacetylation of chitosan is 95%. (3) The polymer emulsion and hyaluronic acid solution were mixed at a mass ratio of 9:1, sodium dodecyl sulfate was added, and the mixture was stirred for 2 hours. Then, under nitrogen protection, the mixture was reacted at 80°C for 1.5 hours, heated to 90°C, and reacted for another 1.5 hours. The mixture was then filtered and dried under vacuum at 80°C to obtain intermediate microspheres. The amount of sodium dodecyl sulfate used was 10% of the total weight of the polymer emulsion and hyaluronic acid solution. (4) Add the intermediate microspheres to a 0.5 mol / L sodium hydroxide solution, heat to 80°C, stir for 38 h, filter, wash with distilled water until neutral, and dry at 70°C to obtain PMMA microspheres.

[0037] Preparation Example 8: The difference from Preparation Example 6 is that chitosan was not added.

[0038] Preparation Example 9: The difference from Preparation Example 6 is that the intermediate microspheres were not heated in sodium hydroxide solution, and the intermediate microspheres were PMMA microspheres.

[0039] Preparation Example 10: (1) 0.15 kg chitosan, 0.1 kg potassium persulfate and 1 kg methyl methacrylate were mixed and stirred evenly at 70 °C for 12 h to obtain a polymer emulsion. The mass ratio of methyl methacrylate, chitosan and potassium persulfate was 1:0.15:0.1 and the degree of deacetylation of chitosan was 95%. (2) Sodium dodecyl sulfate was added to the polymer emulsion and stirred for 2 hours. Then sodium chloride was added to break the emulsion. The emulsion was washed with distilled water and dried under vacuum to obtain PMMA microspheres. The amount of sodium dodecyl sulfate was 9% of the total weight of the polymer emulsion. Example

[0040] Example 1: A super-retarded concrete, the raw material dosages are shown in Table 1, wherein the cement is P.O42.5 silicate cement, the aggregate is 5-16mm continuously graded crushed stone with a mud content of 0.25% and a mud lump content of 0.15%, the sand is zone II medium sand with a fineness modulus of 2.3 and a mud content of 2%, the admixture is grade II fly ash with a fineness of 13%, the water requirement ratio is 95%, the loss on ignition is 2%, the corrosion inhibitor is sodium benzoate, the lubricant is sodium rosinate, and the retarder is prepared by mixing the following raw materials by weight: 150g wheat straw alkali The ingredients include a solution, 150g of polycarboxylate slump retainer, 60g of white sugar, 30g of sodium gluconate, 0.05g of sodium dodecyl sulfate, and 0.05g of hydroxypropyl methylcellulose. The polycarboxylate slump retainer is selected from Liaoning Kelong Fine Chemical Co., Ltd., model SPS-100, and the hydroxypropyl methylcellulose is selected from Zhongmu Chemical Materials Co., Ltd. in Longting District, Kaifeng City, model 0909. The wheat straw alkali solution is prepared by the following method: the wheat straw is crushed, soaked in a 5wt% sodium hydroxide solution for 12 hours, removed, filtered, and the filtrate is the wheat straw alkali solution.

[0041] The above-mentioned method for preparing super-retarded concrete includes the following steps: (1) Mix cement, gravel, sand and admixtures evenly to obtain dry mix; (2) The retarder, preservative and lubricant are mixed to prepare a composite additive; (3) Add the composite admixture to the dry mix, mix well, add water, stir evenly, and obtain super slow-setting concrete.

[0042] Table 1. Raw material consumption of super-retarded concrete in Examples 1-4

[0043] Example 2: A super-retarded concrete, differing from Example 1 in that the concrete raw material quantities are as shown in Table 1. The cement is P.O42.5 silicate cement, the aggregate is 5-16mm continuously graded crushed stone with a mud content of 0.25% and a mud lump content of 0.15%, the sand is zone II medium sand with a fineness modulus of 2.3 and a mud content of 2%, the admixture is grade II fly ash with a fineness of 13%, the water requirement ratio is 95%, the loss on ignition is 2%, the preservative is citric acid, the lubricant is sodium rosinate, and the retarder is prepared by mixing the following raw materials by weight: The ingredients are 150g wheat straw alkali solution, 150g aminosulfonate type slump retainer, 60g white sugar, 30g sodium gluconate, 0.05g sodium dodecyl sulfate and 0.05g hydroxypropyl methylcellulose. The aminosulfonate type slump retainer is selected from Laiwu Yanhui Building Materials, model BHY-2, and the hydroxypropyl methylcellulose is selected from Kaifeng Longting District Zhongmu Chemical Materials, model 0909. The wheat straw alkali solution is prepared by the following method: the wheat straw is crushed, soaked in a 4wt% sodium hydroxide solution for 10 hours, taken out, filtered, and the filtrate is the wheat straw alkali solution.

[0044] Example 3: A super-retarded concrete, differing from Example 1 in that the raw material quantities are as shown in Table 1. The cement is P.O42.5 silicate cement, the aggregate is 5-16mm continuously graded crushed stone with a mud content of 0.25% and a mud lump content of 0.15%, the sand is zone II medium sand with a fineness modulus of 2.3 and a mud content of 2%, the admixture is grade II fly ash with a fineness of 13%, the water requirement ratio is 95%, the loss on ignition is 2%, the corrosion inhibitor is sodium selenite, the lubricant is sodium rosinate, and the retarder is a mixture of the following raw materials by weight. The following ingredients were prepared: 150g wheat straw alkali solution, 150g naphthalene-based slump retainer, 60g white sugar, 30g sodium gluconate, 0.05g sodium dodecyl sulfate, and 0.05g hydroxypropyl methylcellulose. The naphthalene-based slump retainer was selected from Shanghai Lingyu Building Materials, model 1214-10, and the hydroxypropyl methylcellulose was selected from Kaifeng Longting District Zhongmu Chemical Materials, model 0909. The wheat straw alkali solution was prepared by the following method: the wheat straw was crushed, soaked in a 5wt% sodium hydroxide solution for 12 hours, removed, filtered, and the filtrate was obtained as the wheat straw alkali solution.

[0045] Example 4: An ultra-retarded concrete, which differs from Example 1 in that the raw material dosage is shown in Table 1.

[0046] Examples 5-7: A super-retarded concrete, which differs from Example 1 in that the raw materials and dosage of the retarder are shown in Table 2.

[0047] Table 2. Raw material dosage of retarders in Examples 1 and 5-7

[0048] Example 8: An ultra-retarded concrete, which differs from Example 1 in that the lubricant is made from Preparation Example 1.

[0049] Example 9: An ultra-retarded concrete, which differs from Example 1 in that the lubricant is made from Preparation Example 2.

[0050] Example 10: An ultra-slow-setting concrete, which differs from Example 1 in that the lubricant is made from Preparation Example 3.

[0051] Example 11: An ultra-retarded concrete, which differs from Example 1 in that the lubricant is made from Preparation Example 4.

[0052] Example 12: An ultra-slow-setting concrete, which differs from Example 1 in that the lubricant is made from Preparation Example 5.

[0053] Example 13: An ultra-retarded concrete, which differs from Example 8 in that the admixture includes fly ash and PMMA microspheres in a mass ratio of 1:1. The PMMA microspheres are selected from Suzhou Zhiyi Microsphere Technology Co., Ltd., model KBsphere®70PMMA, the fly ash has a particle size of 32μm, and the PMMA microspheres have a particle size of 70μm.

[0054] Example 14: An ultra-retarded concrete, which differs from Example 8 in that the admixture includes fly ash and PMMA microspheres in a mass ratio of 1:1. The PMMA microspheres are prepared by Preparation Example 6, with the fly ash having a particle size of 32 μm and the PMMA microspheres having a particle size of 70 μm.

[0055] Example 15: An ultra-retarded concrete, which differs from Example 8 in that the admixture includes fly ash and PMMA microspheres in a mass ratio of 1:0.5. The PMMA microspheres are prepared in Preparation Example 7, with the fly ash having a particle size of 35 μm and the PMMA microspheres having a particle size of 65 μm.

[0056] Example 16: An ultra-retarded concrete, which differs from Example 14 in that the PMMA microspheres are made from Preparation Example 8.

[0057] Example 17: An ultra-retarded concrete, which differs from Example 14 in that the PMMA microspheres are made from Preparation Example 9.

[0058] Example 18: An ultra-retarded concrete, which differs from Example 14 in that the PMMA microspheres are made from Preparation Example 10.

[0059] Comparative Example Comparative Example 1: An ultra-retarded concrete, which differs from Example 1 in that no lubricant was added to the concrete.

[0060] Comparative Example 2: An ultra-retarded concrete, which differs from Example 1 in that no wheat straw alkali solution was added to the retarder.

[0061] Comparative Example 3: An ultra-retarded concrete, which differs from Example 1 in that sodium dodecyl sulfate was not added to the retarder.

[0062] Comparative Example 4: An ultra-retarded concrete, which differs from Example 1 in that the retarder is entirely sodium gluconate.

[0063] Performance testing Super-retarded concrete was prepared according to the methods in the examples and comparative examples, and its performance was tested according to the following methods. The test results are recorded in Table 3.

[0064] 1. Retarding time: Tested in accordance with GB / T8076-2008 "Concrete Admixtures".

[0065] 2. Compressive strength: Tested in accordance with GB / T50080-2016 "Test Methods for Performance of Ordinary Concrete Mixtures".

[0066] 3. Slump: Tested in accordance with GB / T50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures".

[0067] 4. Drying Shrinkage Test: The concrete prepared in the embodiments and comparative examples of this application was tested according to the non-contact test method in GB / T50082-2009 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete". The 28-day drying shrinkage value (10... -6 ).

[0068] Table 3 Performance testing of super-retarded concrete

[0069] As can be seen from the data in Table 3, the super-retarded concrete prepared by using different amounts of raw materials in Examples 1-4 has a longer setting time, which can provide operators with enough time to adjust and control during construction. In addition, it has a large slump and good fluidity.

[0070] Examples 5-7 use a different retarder formulation than Example 1. The resulting super-retarded concrete is similar to that of Example 1, with good retarding effect and fluidity.

[0071] In Examples 8 and 9, the lubricants prepared in Preparation Example 1 and Preparation Example 2 were used, respectively. As shown in Table 3, the setting time of the ultra-retarded concrete prepared in Examples 8 and 9 did not change much, but the slump increased, the fluidity was significantly enhanced, and the drying shrinkage rate decreased.

[0072] In Examples 10 and 11, the lubricants prepared in Preparation Example 3 and Preparation Example 4 were used respectively. Polyalphaolefin and PTFE micro powder were used alone, respectively. The fluidity of the concrete deteriorated, and the drying shrinkage rate increased in Example 11.

[0073] In Example 12, the lubricant prepared in Preparation Example 5 was used. A mixture of PTFE micropowder and polyalphaolefin was used as the lubricant. As shown in Table 3, the concrete prepared in Example 12 had a reduced slump and decreased compressive strength.

[0074] Compared with Example 8, Example 13 also uses fly ash and PMMA microspheres as admixtures. As shown in Table 3, the compressive strength of the super-retarded concrete prepared in Example 13 is increased, as is the slump and fluidity.

[0075] In Examples 14 and 15, PMMA microspheres prepared in Preparation Examples 6 and 7 were added, respectively. Compared with Example 8, the super-retarded concrete prepared in Examples 14 and 15 showed increased fluidity and reduced drying shrinkage.

[0076] In Example 16, PMMA microspheres prepared in Preparation Example 8 were used without the addition of chitosan. Compared with Example 14, the concrete prepared in Example 16 showed reduced drying shrinkage, while other properties remained largely unchanged.

[0077] In Example 17, PMMA microspheres prepared in Preparation Example 9 were used, but no sodium hydroxide solution treatment was performed compared to Example 14. In Example 18, PMMA microspheres prepared in Preparation Example 10 were used. Compared to Example 14, the drying shrinkage of the super-retarded concrete prepared in Examples 17 and 18 was increased.

[0078] No lubricant was added in Comparative Example 1. As shown in Table 3, the super-retarded concrete prepared in Comparative Example 1 had poorer fluidity and a slightly faster setting time.

[0079] In Comparative Example 2, no wheat straw alkali solution was added to the retarder; in Comparative Example 3, no sodium dodecyl sulfate was added to the retarder. As can be seen from the data in Table 3, compared with Example 1, the concrete prepared in Comparative Example 2 and Comparative Example 3 had shorter setting times. Moreover, the compressive strength of Comparative Example 2 was weakened and the slump was reduced, while the slump of Comparative Example 3 was reduced and the fluidity was worse.

[0080] In Comparative Example 4, sodium gluconate was used as a retarder. As shown in Table 3, compared with Example 1, the concrete prepared in Comparative Example 4 had a shorter setting time, poorer fluidity, and decreased compressive strength.

[0081] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A super-retarded concrete, characterized in that, The raw materials include the following parts by weight: 165-175 parts water, 160-260 parts cement, 983-1000 parts gravel, 830-845 parts sand, 110-160 parts admixture, 3-6 parts retarder, 2-5 parts preservative, and 10-20 parts lubricant. The retarder comprises the following raw materials in parts by weight: 150-200 parts wheat straw alkali solution, 150-200 parts slump retainer, 60-80 parts white sugar, 30-50 parts sodium gluconate, 0.05-0.08 parts sodium dodecyl sulfate, and 0.05-0.1 parts hydroxypropyl methylcellulose; The lubricant is prepared as follows: PTFE micro powder and polyalphaolefin are mixed evenly to prepare a matrix solution; Hexadecyltrimethylammonium bromide was added to a mixed solution of anhydrous ethanol and deionized water, and stirred to dissolve, thus obtaining a mixed solution. The matrix solution is added to the mixture, homogenized, sonicated, and the pH is adjusted to 10-11. The mixture is heated in a water bath to 80-85℃, tetraethyl orthosilicate is added, and the mixture is stirred for 1-2 hours. After cooling to room temperature, the mixture is filtered, washed, and dried to obtain the lubricant. The admixture comprises fly ash and PMMA microspheres in a mass ratio of 1:0.5-1; The PMMA microspheres are prepared as follows: Hyaluronic acid is added to deionized water to obtain a hyaluronic acid solution; Chitosan, potassium persulfate, and methyl methacrylate are mixed and stirred evenly at 70-80℃ to obtain a polymer emulsion. The mass ratio of methyl methacrylate, chitosan, and potassium persulfate is 1:0.1-0.15:0.1-0.

2. The polymer emulsion and hyaluronic acid solution were mixed at a mass ratio of 9-10:1, sodium dodecyl sulfate was added, and the mixture was stirred evenly. Then, under nitrogen protection, the mixture was reacted at 75-80℃ for 1.5-2 hours, and the temperature was raised to 85-90℃ for 1.5-2 hours. The mixture was then filtered and dried to obtain intermediate microspheres. The intermediate microspheres were added to a sodium hydroxide solution, heated to 80-85℃, stirred for 38-40 hours, filtered, washed until neutral, and dried to obtain PMMA microspheres.

2. The super-retarded concrete according to claim 1, characterized in that: The mass ratio of PTFE micro powder to polyalphaolefin is 0.2-0.4:1; The mass ratio of the matrix solution, hexadecyltrimethylammonium bromide, and tetraethyl orthosilicate is 1:0.3-0.35:1-1.

2.

3. The super-retarded concrete according to claim 1, characterized in that: The fly ash has a particle size of 32-35 μm, and the PMMA microspheres have a particle size of 65-70 μm.

4. The super-retarded concrete according to claim 1, characterized in that: The wheat straw alkali solution is obtained by crushing wheat straw, soaking it in sodium hydroxide solution, and then taking it out.

5. The super-retarded concrete according to claim 1, characterized in that: The preservative is selected from at least one of nitrates, nitrites, sodium benzoate, and citric acid.

6. The super-retarded concrete according to claim 1, characterized in that: The slump retainer is at least one of polycarboxylate slump retainers, aminosulfonate slump retainers, and naphthalene-based slump retainers.

7. The method for preparing the super-retarded concrete according to any one of claims 1-6, characterized in that: Includes the following steps: Cement, gravel, sand, and admixtures are mixed evenly to obtain a dry mix. A composite additive is prepared by mixing retarder, preservative and lubricant; The composite admixture is added to the dry mix, mixed well, and then water is added and stirred evenly to obtain super-retarded concrete.

Citation Information

Patent Citations

  • Super-retarding concrete and preparation method thereof

    CN116283133A

  • Chitosan microcapsule modified acrylic bone cement and preparation method thereof

    CN113384747A

  • Super-retarding anti-crack concrete and preparation method thereof

    CN115959862A